The public perception towards electoral redelineation process in Sabah / Nik Farah Dianah Nik Mohd Kamal and Nur Amalina Abdul Jalil - Nik Mohd Kamal, Nik Farah Dianah; Abdul Jalil, Nur Amalina (2016)
Redelineation process is the important part before the new election. Public always confuse about this process because it always do not tally with the benefits on the both part. This study focuses finding a Chi Square test based on the factors that affect public perceptions. These factors are independency of Election Commission, the influences of political parties, and level of political awareness of the public. Furthermore, this study also can be used by the university in order to give better understanding about the redelineation process factors that affect public perceptions in Kota Kinabalu, Sabah. . However, the study was limited by the limited area that only focuses in one state that is Kota Kinabalu, Sabah. At the end of this study, it was found that the factors (independency of Election Commission, the influences of political parties and level of political awareness of the public) contributed significantly to the public perceptions.